EFFECTIVENESS OF HOTS LEARNING CONCEPT WITH THE IMPLEMENTATION OF INDEPENDENT CURRICULUM IN ELEMENTARY SCHOOL - Abakar, Ali Abakar Ben (Edu Learning, 2025)
This study aims to describe the relevance of High Order Thinking Skills (HOTS)-based learning in elementary schools with the implementation of the Merdeka Curriculum at the elementary school level. It is well known that the Merdeka Curriculum is the latest curriculum implemented in educational institutions, and the HOTS learning concept is still being implemented recently. Therefore, it is necessary to conduct a study in the form of research to see the effectiveness of the relevance of the HOTS learning concept to the Merdeka Curriculum in elementary schools. This research is a descriptive research with a qualitative approach. There are 2 methods used, namely descriptive and evaluative methods. The research population is the elementary school level. Data was collected using related and current literature studies. The results showed that the application of HOTS significantly improved students' learning motivation and concept understanding, and encouraged them to more actively participate in class discussions. In addition, students showed improvement in critical and creative thinking skills. Despite challenges in implementation, such as the lack of training for teachers, these positive results confirm the importance of HOTS integration in the Merdeka Curriculum to improve the quality of education at the primary school level.